THE DETERMINANTS OF TAX AVOIDANCE: THE ROLE OF RETURN ON ASSETS AND COMPANY SIZE IN THE FINANCIAL SECTOR IN INDONESIA - Iyaza Zumariz; Sofie Yunida Putri (RISTANSI: Riset Akuntansi, 2026)
This study explores tax avoidance as a complex issue among large corporations, with an emphasis on the influence of ROA and Firm Size on such practices. Using a quantitative approach, the analysis was conducted on 248 financial statement from financial sector companies listed on the Indonesia Stock Exchange year 2020 to 2023 observations selected purposive sampling. The data were processed using panel data regression analysis with EViews 13. The findings indicate that ROA has a significant effect on tax avoidance, where companies with higher ROA tend to engage more actively in tax planning to maintain profitability. Additionally, firm size also plays a role in tax avoidance, as larger companies have better access to resources and information, enabling them to design more effective tax strategies. These results affirm that both ROA and firm size are important factors to consider in managing tax obligations, with significant implications for management in enhancing company value and maintaining a positive financial image in the eyes of investors.